CSF1R Stimulation Promotes Increased Neuroprotection by CD11c+ Microglia in EAE - Wlodarczyk, Agnieszka; Benmamar-Badel, Anouk; Cédile, Oriane; Jensen, Kirstine Nolling; Kramer, Isabella; Elsborg, Nick Boe; Owens, Trevor (Frontiers in Cellular Neuroscience, 2019)
Microglia are resident immune cells of the central nervous system. Their development and maintenance depend on stimulation of Colony Stimulating Factor-1 receptor (CSF1R). Microglia play an important role in neurodevelopment and a population of microglia that expresses the complement receptor CD11c is critical for primary myelination. This population is virtually absent in the healthy adult brain but increases dramatically upon neuroinflammatory conditions, and these microglia are suggested to play a protective role in central nervous system (CNS) diseases. To date, the molecular trigger for their expansion is unknown. Here we showed that stimulation of CSF1R by either of its ligands, CSF1 and interleukin (IL)-34, can induce expansion of CD11c+ microglia. In addition, such stimulation resulted in amelioration of EAE symptoms and decreased demyelination. Treatment with CSF1R ligands also induced expression of the chemokine CCL2, and we showed that experimental overexpression of CCL2 in the brain led to a dramatic increase of CD11c+ microglia, independent of CCR2. Moreover, this led to elevated CSF1 expression, suggesting a positive feedback loop between CSF1R and CCL2. These data provide new insights to microglia biology and open new perspectives for modulating microglial activity in neuroinflammatory diseases such as multiple sclerosis.